Information Acquisition and Exchange in Social Networks. (7th April 2017) - Goyal, Sanjeev; Rosenkranz, Stephanie; Weitzel, Utz; Buskens, Vincent
Abstract : A central feature of social networks is information sharing. The Internet and related computing technologies shape the relative costs of private information acquisition and forming links with others. This article presents an experiment on the effects of changing costs. We find that a decline in relative costs of linking makes private investments more dispersed and gives rise to denser social networks. Aggregate investment falls but individuals' access to investment remains stable, due to increased networking. The overall effect is an increase in individual utility and aggregate welfare.